2013
DOI: 10.1080/13546805.2013.854199
|View full text |Cite
|
Sign up to set email alerts
|

Failure to benefit from target novelty during encoding contributes to working memory deficits in schizophrenia

Abstract: Introduction Although working memory (WM) impairments are well documented in schizophrenic patients (PSZ), the underlying mechanisms are poorly understood. The aim of this study was to investigate the role of target salience during encoding to determine whether impaired visual attention in PSZ leads to poor WM. Methods 31 PSZ and 28 demographically matched healthy controls (HC) performed a spatial delayed-response task. Attentional demands were manipulated during WM encoding by presenting high salient (novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
5
12
1
1
Order By: Relevance
“…In line with the encoding hypothesis, we have also shown that the percentage of incorrect/confident (IC) responses in a visuo-spatial delayed response task decreased when the processes that support WM encoding were facilitated (Mayer et al, 2011). Furthermore, this behavioral approach has been useful to dissociate encoding and maintenance deficits in patients with schizophrenia Mayer et al, 2014Mayer et al, , 2018.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In line with the encoding hypothesis, we have also shown that the percentage of incorrect/confident (IC) responses in a visuo-spatial delayed response task decreased when the processes that support WM encoding were facilitated (Mayer et al, 2011). Furthermore, this behavioral approach has been useful to dissociate encoding and maintenance deficits in patients with schizophrenia Mayer et al, 2014Mayer et al, , 2018.…”
Section: Introductionsupporting
confidence: 65%
“…One issue that complicates the investigation of failures in processes related specifically to WM encoding is the difficulty of isolating the encoding process in behavioral paradigms because performance measures (i.e., accuracy and reaction time) are compound measurements that potentially reflect processes associated with all different task phases (i.e., encoding, maintenance, and retrieval). In order to isolate WM encoding processes, we previously introduced a novel behavioral approach based on the analysis of different types of correct and erroneous responses depending on the trial-to-trial level of self-reported subjective response confidence (Lee et al, 2008;Mayer et al, 2011Mayer et al, , 2014Mayer et al, , 2018Rademaker et al, 2012;Peters et al, 2019). Specifically, we reasoned that incorrect responses that were, however, given with confidence most likely reflect a problem at the encoding stage.…”
Section: Introductionmentioning
confidence: 99%
“…Novel stimuli thus attract attention, also when there is no incentive to pay attention to them, and even when performance on ongoing tasks suffers. Consistent with novel stimuli attracting attention, novel stimuli are encoded better into visual working memory than familiar ones (Mayer et al, 2011(Mayer et al, , 2014. Mayer and colleagues suggested that this effect was mediated by more efficient allocation of attentional resources to novel than to familiar items, rather than to low-level stimulus characteristics.…”
Section: Attention To Noveltymentioning
confidence: 92%
“…We argue that this mechanism may be distinct from the case of the rodent NOR test, where slowly decaying (up to 24 h) episodic-like memory appears to operate [14] (but for alternative interpretations, see [69]). A model that potentially involves alterations in primary sensory processing could be useful for modeling deficits in "bottom-up" processes that have been described in schizophrenics, including deficits in habituation and automatic responses to novelty [10,27,43,45,65]. Some of these sensory processing deficits have been strongly associated with negative symptom scores [10,13,27,68].…”
Section: Discussionmentioning
confidence: 96%